2010
DOI: 10.1002/jcp.22289
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipopolysaccharide‐induced inflammatory response and endotoxemia by β‐arrestins

Abstract: β-arrestins are scaffolding proteins implicated as negative regulators of TLR4 signaling in macrophages and fibroblasts. Unexpectedly, we found that β-arrestin-1 (β-arr-1) and −2 knockout (KO) mice are protected from TLR4-mediated endotoxic shock and lethality. To identify the potential mechanisms involved, we examined the plasma levels of inflammatory cytokines/chemokines in the wild type (WT) and β-arr-1 and −2 KO mice after lipopolysaccharide (LPS, a TLR4 ligand) injection. Consistent with lethality, LPS-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 63 publications
1
50
3
Order By: Relevance
“…Afterward, other findings indicated that the functions of b-arrestins are pleiotropic (35,36). Nevertheless, we found that b-arrestin1 had no effect on IL-6 and pro-IL-1b production, but it regulated IL-1b secretion by regulating inflammasome activation.…”
Section: Discussioncontrasting
confidence: 47%
“…Afterward, other findings indicated that the functions of b-arrestins are pleiotropic (35,36). Nevertheless, we found that b-arrestin1 had no effect on IL-6 and pro-IL-1b production, but it regulated IL-1b secretion by regulating inflammasome activation.…”
Section: Discussioncontrasting
confidence: 47%
“…NMDA activation-induced dendrite spine remodeling in neurons is dependent on the scaffolding protein ␤-arrestin-2 (24). This was of interest because ␤-arrestin-2 is known to modulate LPS-induced inflammatory responses, but its role in inflammasome activation is not known (5,22,25,33). Our results clearly show that aspartate-dependent downregulation of inflammasome function in vitro and in vivo is dependent on ␤-arrestin-2.…”
Section: G735mentioning
confidence: 59%
“…22 Using a well-established cellular model of inflammation, the aim of the present work was to evaluate the potential of a G i inhibitor encapsulated in Lipo in reducing the inflammatory effects induced by LPS in monocytes/macrophages, such as the activation of MAPK-signaling pathways, inflammatory cytokine secretion, monocyte adhesion, and chemotaxis. 23 G proteins are heterotrimers comprising α-, β-, and γ-subunits that dissociate in response to proinflammatory stimuli after activation of G-protein-coupled receptors. The free G α and G βγ subunits can then activate different mediators Figure 5 effect of lipo/gOT on monocyte adhesion to endothelium.…”
Section: Discussionmentioning
confidence: 99%